HUBUNGAN BEBAN KERJA DAN LINGKUNGAN KERJA DENGAN TINGKAT STRES PERAWAT DI RS X KOTA BATAM - Junaidah, Junaidah; Wardhani, Utari Christya; Muharni, Sri (Jurnal Sains, Teknologi dan Kesehatan, 2023)
The Indonesian National Nurses Association revealed that as many as 50.9% of Indonesian nurses who work experience work stress, often feel dizzy, tired, unfriendly, lack of rest due to too high workload and inadequate income. Factors that cause work stress include workload and work environment. Workloads that are heavy and too high can make nurses feel overwhelmed. A conducive work environment will support the smooth work carried out by nurses. The purpose of this study was to see the relationship between the workload of nurses, work environment and work stress in hospitals. X Batam City. The research design used was cross sectional with a total sampling technique of 54 nurses. The results of the bivariate analysis between workload and work environment with work stress using the Chi-square Statistical Test obtained p-value 0.000 <0.05 which means Ha is accepted and Ho can be concluded that there is a significant relationship between workload, work environment and work stress in the hospital X Batam. It is expected that the hospital can provide a comfortable work environment to support the productivity of nurses and pay attention to the workload of nurses to avoid work stress in the hospital.